An AI system to help scientists write expert-level empirical software - Eser Aygün; Anastasiya Belyaeva; Gheorghe Comanici; Marc Coram; Hao Cui; Jake Garrison; Renee Johnston; Anton Kast; Cory Y. McLean; Peter Norgaard; Zahra Shamsi; David Smalling; et al. (Nature, 2026)
Abstract The cycle of scientific discovery is frequently bottlenecked by the slow, manual creation of software to support computational experiments 1 . To address this, we present Empirical Research Assistance (ERA), an artificial intelligence (AI) system that creates expert-level scientific software whose goal is to maximize a quality metric. The system uses a large language model (LLM) and tree search 2 to systematically improve the quality metric and intelligently navigate the large space of possible solutions. ERA achieves expert-level results when it explores and integrates complex research ideas from external sources. The effectiveness of tree search is demonstrated across a diverse range of tasks. In bioinformatics, ERA discovered 40 new methods for single-cell data analysis that outperformed the top human-developed methods on a public leaderboard. In epidemiology, ERA generated 14 models that outperformed the Centers for Disease Control and Prevention (CDC) ensemble and all other individual models for forecasting COVID-19 hospitalizations. ERA also produced expert-level software for geospatial analysis, neural activity prediction in zebrafish and numerical solution of integrals, as well as a new rule-based construction for time-series forecasting. By devising and implementing new solutions to diverse tasks, ERA represents a notable step towards accelerating scientific progress.